Assessment of Simple Engineering Approaches and Poultry Manure for Soil Erosion Control Under Maize Cultivation in the Tropics - Olanrewaju Hameed Ologunde; Sodiq Dimeji Akanni; Abdullahi Bamidele Olayemi; Mutiu Abolanle Busari (Air, Soil and Water Research)
Monitoring soil erosion is crucial for soil conservation policies, especially in tropical regions that are prone to water erosion. A 2-year field study was conducted to assess the impact of simple engineering approaches and poultry manure application on soil loss, soil physical properties, maize yield, and economic benefit in Southwest Nigeria. The experiment was a 4 × 2 factorial arrangement with three replications. The treatments included four engineering approaches (surface mat, silt fencing, furrow dike, and no approach [control]) and two poultry manure application rates at 0 and 20 t ha −1 . Annual soil loss was higher under the control (6.22–8.01 Mg ha −1  year −1 ). The combination of engineering approaches with poultry manure at 20 t ha −1 significantly ( p  ⩽ .05) reduced soil loss by 9.7% to 85.4% compared to control. Engineering approaches and poultry manure application did not significantly improve soil physical properties; however, saturated hydraulic conductivity was highest under surface mat combined with poultry manure at 20 t ha −1 in both years. Maize yield increased by 27.7% under surface mat compared to control, while an additional grain yield of 0.14 Mg ha −1 was obtained for 20 t ha −1 poultry manure over 0 t ha −1 . Soil loss was negatively and significantly correlated with grain yield. The results suggest that integrating surface mats with poultry manure can be effective in controlling soil loss, enhancing soil properties, and improving maize yield.